Analisis Pemborosan Pada Proses Aliran Pergudangan PT. FLSmidth Indonesia dengan Metode Lean Warehousing - Adinda Laksmi Pratiwi; Endang Pudji Widjajati (Pusat Riset dan Inovasi Nasional, 2023)
FLSmidth Indonesia still has various wasteful activities in the spare-part warehousing flow process. This study was conducted with the aim of knowing the kinds of waste that occur and the proposed improvements that can be given. The analysis in this study uses the lean warehousing method which consists of Waste Assessment Model (WAM), Value Stream Mapping (VSM), Value Stream Analysis Tools (VALSAT), and Fishbone Diagram. This study provides the results of the total percentage of important non-value-added activities and non-value-added activities is 50% or equivalent to the percentage of value-added activities, as well as a total lead time of 7448 minutes. After analyzing improvements using Process Activity Mapping (PAM) and fishbone diagrams, it was found that the percentage of value-added activities increased to 56% and the total lead time changed to 7648 minutes.